A phase 3 trial of safety, tolerability, and immunogenicity of V114, 15-valent pneumococcal conjugate vaccine, compared with 13-valent pneumococcal conjugate vaccine in adults 50 years of age and older (PNEU-AGE). Issue 1 (3rd January 2022) - Platt, Heather L.; Cardona, Jose F.; Haranaka, Miwa; Schwartz, Howard I.; Narejos Perez, Silvia; Dowell, Anthony; Chang, Chih-Jen; Dagan, Ron; Tamms, Gretchen M.; Sterling, Tina; Morgan, Leslie; Shi, Yaru; et al.
Highlights: The safety results in this study were consistent with the safety profile of PCV vaccines in adults. Noninferior immunogenicity was demonstrated for each of the 13 shared serotypes (ST) in V114 compared to PCV13. In addition to non-inferiority, superiority was also analyzed for shared ST3. Superior immunogenicity of V114 compared to PCV13 was demonstrated for shared ST3, and two serotypes unique to V114 (ST22F, and ST33F). Abstract: Background: Pneumococcal conjugate vaccines (PCVs) have greatly reduced the incidence of pneumococcal disease, yet unmet medical need remains due to increased disease caused by non-vaccine serotypes (STs). V114 (VAXNEUVANCE TM, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA) is a 15-valent PCV containing 13 serotypes in licensed PCV13 and 2 additional serotypes (22F, 33F) which significantly contribute to pneumococcal disease burden. This phase 3 trial compared safety, tolerability, and immunogenicity of V114 to PCV13 in adults ≥50 years of age. Methods: Adults were randomized 1:1 to receive a single dose of V114 or PCV13; randomization was stratified by age (50–64 years, 65–74 years, and ≥75 years). Adverse events (AEs) were collected following vaccination. Serotype-specific opsonophagocytic activity (OPA) and immunoglobulin G (IgG) antibodies were measured prior to and 30 days after vaccination (Day 30). Primary objectives included assessing noninferiority of V114 to PCV13 for the 13 shared serotypes and superiority of V114 to PCV13 for the two unique serotypes. Superiority of V114 to PCV13 for shared serotype 3 was assessed as a secondary objective. Results: Overall, 1, 202 participants were vaccinated (V114 N = 602, PCV13 N = 600). The most commonly reported AEs across both groups were injection-site pain, fatigue, and myalgia. V114 met noninferiority criteria compared to PCV13 for the 13 shared serotypes (using a 2-fold non-inferiority margin for the ratio of OPA geometric mean titers [GMTs] [V114/PCV13] at Day 30) and met superiority for the 2 unique serotypes (using a 2-fold super-superiority margin for the ratio of OPA GMTs [V114/PCV13] at Day 30 and a 0.10 super-superiority margin for the difference in proportions of participants with ≥4-fold rise from prevaccination to Day 30). V114 met superiority criteria compared to PCV13 for serotype 3 (based on a super-superiority margin of 1.2 for the ratio of the OPA GMTs [V114/PCV13] and a superiority margin of 0 for the difference in proportions of participants with ≥4-fold rise). [NCT03950622, EudraCT#2018-004316-22, Japic-CTI#194845].